Critical Analysis of the Modernisation of Madrasah Human Resource Development - Firmansyah, Firmansyah; Adam, Saed M; Fridiyanto, Fridiyanto; Dharmawan, Arief (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The purpose of this research is to analyse how the modernisation of HR development at MTsN 1 Padangsidimpuan. This research is a qualitative field research using a descriptive approach. Data collection instruments are observation or observation, interviews, and documentation. Research informants were the head of the madrasah, the deputy head of curriculum, the deputy head of public relations, the deputy head of student affairs, the subject teachers, and the head of administration. The analysis technique in this study adopted the stages proposed by Creswell, namely data analysis starting with data collection, then continued with data classification, namely the selection and concentration of attention on the focus being studied. The data analysis process was carried out continuously throughout the research. The results of this study are the development of human resources (HR) at MTsN 1 Padangsidimpuan, carried out through several approaches that support each other. The efforts made include training, mentoring, MGMP (Subject Teacher Consultation), and the implementation of On-the-Job Training (OJT). Each approach has an important role in improving the competence and professionalism of educators and education personnel in this school. Through regular training, mentoring, subject teacher meetings (MGMP), and on-the-job training (OJT), educators in this madrasah can improve their pedagogic competence and professionalism. As a result, the quality of teaching becomes more innovative, interactive, and relevant to the times. This approach also strengthens collaboration among teachers and improves school management, creating a dynamic and quality educational environment.